Effectiveness of Indigenous Lead (Pb) Reducing Bacteria Consortia of Waste Water Treatment in Agar Flour Industry - Sa'diyah, Wasiatus; Suarsini, Endang; Ibrohim, Ibrohim (Graduate School, Universitas Brawijaya, 2016)
Lead (Pb) is known as toxic element in environment. It is produced from processing of Agar Flour industry activities. Enhancement of Pb in the waste water of agar flour is very dangerous for human health. Effect of lead damage some organ e.g. kidney, liver, and hair. Environment standard of lead concentration on waste water based on Governor of East Java Regulation No. 72 of 2013 is 1 mg.L-1, otherwise, initial lead levels of waste water are 3.114 mg.L-1. The aim of the research is reducing the level of lead to be harmless for the environment. One method to decrease a high concentration of lead in waste water is biosorption. Consortia of Bacillus alvei and Bacillus pumilus as indigenous bacteria are used to decrease Pb level in the wastewater. The experiment was carried out with varies of wastewater concentration and bacteria 3 %, 4%, 5%, 6%, and 7%. Consortium of B. alvei dan B. pumilus at 7 % concentration have the highest potency 93.58 % to reduce lead reach 0.2 mg.L-1.Keywords: Bacteria, Consortia, Concentration, Pb, Waste of Agar Flour